Empirical Study on the Obstacles to the Success of Joint Ventures in Construction Projects - Chen Lu; Zhiwei Yu; Xuetong Wang; Yuming Hong (Advances in Civil Engineering)
As an effective way of completing technically complex buildings or large-scale infrastructure projects, a joint venture contracting approach has recently been widely used in the construction industry. However, numerous unfavorable results can occur in practice when undertaking construction joint ventures (CJVs). The contribution of this paper is its exploration of the potential obstacles to CJV practices and identification of the root causes of failure. First, through a literature review, semistructured interviews, and a questionnaire survey, seventeen variables were identified; the top three obstacle variables were (1) inconsistent management styles, (2) incompatible organizational cultures, and (3) organizational policy differences. Second, four grouped factors were extracted: (1) unfair and noneffective management; (2) lack of communication, understanding, and mutual trust; (3) policy, management style, and organizational cultural differences; and (4) potential conflicts beyond the CJV partnership. Finally, several strategies were proposed. The research findings could not only contribute to knowledge of CJVs but also provide valuable insights into promoting broader, better applications of CJV projects and contributing to their success.